Rethinking Computers for Cybersecurity. - Lee, Ruby B. (Computer (00189162), 2015)
Cyberattacks are growing at an alarming rate, even as our dependence on cyberspace transactions increases. Our software security solutions may no longer be sufficient. It is time to rethink computer design from the foundations. Can hardware security be enlisted to improve cybersecurity? The author discusses two classes of hardware security: hardware-enhanced security architectures for improving software and system security, and secure hardware. The Web extra at https://youtu.be/z-c9ACviGNo is a video of a 2006 invited seminar at the Naval Postgraduate School, in which author Ruby B. Lee presents the Secret-Protected (SP) architecture, which is a minimalist set of hardware features that can be added to any microprocessor or embedded processor that protects the "master secrets" that in turn protect other keys and encrypted information, programs and data.